2017
DOI: 10.3389/fpls.2017.00407
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Heme Pocket Structure and Ligand Binding Kinetics of Non-symbiotic Hemoglobins from the Model Legume Lotus japonicus

Abstract: Plant hemoglobins (Hbs) are found in nodules of legumes and actinorhizal plants but also in non-symbiotic organs of monocots and dicots. Non-symbiotic Hbs (nsHbs) have been classified into two phylogenetic groups. Class 1 nsHbs show an extremely high O2 affinity and are induced by hypoxia and nitric oxide (NO), whereas class 2 nsHbs have moderate O2 affinity and are induced by cold and cytokinins. The functions of nsHbs are still unclear, but some of them rely on the capacity of hemes to bind diatomic ligands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…An alternative explanation, however, is that NO 3 − is present in the bacteroids after 3 d ( Arrese-Igor et al , 1998 ), but the generated NO is scavenged by metabolic reactions. Such scavenging may occur by nitrosylation of protein cysteine residues or, most probably, by the NO dioxygenase (NOD) activity of Lb 2+ O 2 that converts NO into NO 3 − in the cytosol of infected cells ( Calvo-Begueria et al , 2017 ). In this scenario, Lb 2+ NO would be detectable in nodules only when at least two mechanisms controlling NO concentration, NOD activity in the cytosol and NirK or Nor activities in the bacteroids, were overwhelmed ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative explanation, however, is that NO 3 − is present in the bacteroids after 3 d ( Arrese-Igor et al , 1998 ), but the generated NO is scavenged by metabolic reactions. Such scavenging may occur by nitrosylation of protein cysteine residues or, most probably, by the NO dioxygenase (NOD) activity of Lb 2+ O 2 that converts NO into NO 3 − in the cytosol of infected cells ( Calvo-Begueria et al , 2017 ). In this scenario, Lb 2+ NO would be detectable in nodules only when at least two mechanisms controlling NO concentration, NOD activity in the cytosol and NirK or Nor activities in the bacteroids, were overwhelmed ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Regulation of ligand binding in support of function has been proposed by the detailed study of bimolecular and geminate ligand rebinding to Atha1 and Atha2 (Bruno et al , ; Spyrakis et al , ). Recently, extensive kinetic studies on the various Glbs of the model legume Lotus japonicus (Calvo‐Begueria et al , ) and Arabidopsis (Mot et al , ) strongly suggest non‐redundant functions.…”
Section: Globins Of Angiospermsmentioning
confidence: 99%
“…According to the biochemical activities of PGBs as NO dioxygenase [EC 1.14.12.17] ( Perazzolli et al., 2004 ), nitrite reductase [EC 1.7.2.1] ( Sturms et al., 2011a ; Tiso et al., 2012 ; Kumar et al., 2016 ), and hydroxylamine reductase [EC 1.7.1.10] ( Sturms et al., 2011b ), they seem to be of general importance for the nitrogen metabolism. Since different PGB isoforms differ in their kinetic properties regarding oxygen and NO binding as well as NO deoxygenase activity ( Smagghe et al., 2008 ; Calvo-Begueria et al., 2017 ; Eriksson et al., 2019 ), inducing the biosynthesis of PGBs and improving the biochemical features for NO-fixation might increase the uptake of atmospheric NO. We demonstrated that overexpression of Arabidopsis PGB 1 and 2 in grey poplar could indeed significantly enhance the NO uptake capacity.…”
Section: Discussionmentioning
confidence: 99%